"Don't let the bedbugs bite!". Issue 7 (July 2015) - Fulton, Mary Jo Anderlonis
<x xml:space="preserve">Abstract</x> With teamwork and critical thinking, nurses discover the source of a persistent bedbug infestation in their facility.